The Large Hadron–Electron Collider at the HL-LHC - Agostini, P.; Aksakal, H.; Apolinario, L.; Goyal, A.; Grames, J.; Granados, E.; Grassellino, A.; Gunaydin, Y. O.; Guo, Y. C.; Guzey, V.; Gwenlan, C.; Hammad, A.; et al. (IOP Publishing, 2021)
Abstract The Large Hadron–Electron Collider (LHeC) is designed to move the field of deep inelastic scattering (DIS) to the energy and intensity frontier of particle physics. Exploiting energy-recovery technology, it collides a novel, intense electron beam with a proton or ion beam from the High-Luminosity Large Hadron Collider (HL-LHC). The accelerator and interaction region are designed for concurrent electron–proton and proton–proton operations. This report represents an update to the LHeC’s conceptual design report (CDR), published in 2012. It comprises new results on the parton structure of the proton and heavier nuclei, QCD dynamics, and electroweak and top-quark physics. It is shown how the LHeC will open a new chapter of nuclear particle physics by extending the accessible kinematic range of lepton–nucleus scattering by several orders of magnitude. Due to its enhanced luminosity and large energy and the cleanliness of the final hadronic states, the LHeC has a strong Higgs physics programme and its own discovery potential for new physics. Building on the 2012 CDR, this report contains a detailed updated design for the energy-recovery electron linac (ERL), including a new lattice, magnet and superconducting radio-frequency technology, and further components. Challenges of energy recovery are described, and the lower-energy, high-current, three-turn ERL facility, PERLE at Orsay, is presented, which uses the LHeC characteristics serving as a development facility for the design and operation of the LHeC. An updated detector design is presented corresponding to the acceptance, resolution, and calibration goals that arise from the Higgs and parton-density-function physics programmes. This paper also presents novel results for the Future Circular Collider in electron–hadron (FCC-eh) mode, which utilises the same ERL technology to further extend the reach of DIS to even higher centre-of-mass energies.
Keywords: energy recovery; lepton nucleus: scattering; parton: distribution function; Deep-inelastic scattering; hiukkasfysiikka; accelerator physics; High Energy Physics - Phenomenology (hep-ph); HEAVY FLAVOR CONTRIBUTIONS; info:eu-repo/classification/ddc/530; deep-inelastic scattering; Accelerator physics; top and electroweak physics; new physics; Physics; ddc:530; STRUCTURE-FUNCTION RATIOS; buildings; Physical sciences; Energy-recovery-linac; High Energy Physics - Phenomenology; electron p: colliding beams; kinematics; final state: hadronic; p: distribution function; beyond Standard Model; vertex: primary; numerical calculations: Monte Carlo; High-lumiLHC; [PHYS.NUCL]Physics [physics]/Nuclear Theory [nucl-th]; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; STRUCTURE-FUNCTION F-2(X; [PHYS.NEXP]Physics [physics]/Nuclear Experiment [nucl-ex]; ion: beam; Deep-Inelastic Scattering; Nuclear Theory (nucl-th); deep inelastic scattering; quantum chromodynamics; Top and Electroweak Physics; Nuclear Physics; high-lumi LHC; resolution; sensitivity; [PHYS.HPHE] Physics [physics]/High Energy Physics - Phenomenology [hep-ph]; energy-recovery-linac; Beyond Standard Model; Higgs; acceptance; [PHYS.NUCL] Physics [physics]/Nuclear Theory [nucl-th]; Nuclear Theory; HIGH-ENERGY FACTORIZATION; Settore PHYS-01/A - Fisica sperimentale delle interazioni fondamentali e applicazioni; Nuclear physics; Higgs; High-lumi LHC; High Energy Physics - Experiment; High Energy Physics - Experiment (hep-ex); electron: linear accelerator; electron hadron: scattering; CERN LHC Coll: upgrade; [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; FCC; Nuclear Experiment (nucl-ex); electron: beam; Nuclear Experiment; lattice; superconductivity; Energy-recoverylinac; Beyond Standard Mode; Nuclear physics; QCD; electron nucleus: colliding beams; parton: density; Energy-Recovery-Linac; NUCLEON STRUCTURE FUNCTIONS; [PHYS.NEXP] Physics [physics]/Nuclear Experiment [nucl-ex]; FOS: Physical sciences; nucleus: structure function; Accelerator Physics; electron p: scattering; TRANSVERSE-MOMENTUM DEPENDENCE; nuclear physics; structure; detector: design; DEEP-INELASTIC-SCATTERING; electroweak interaction; LOOP SPLITTING FUNCTIONS; Top and electroweak physics; High-lumi LHC; CLASSICAL RADIATION ZEROS; calibration; QCD; magnet; High-Lumi LHC; [PHYS.HPHE]Physics [physics]/High Energy Physics - Phenomenology [hep-ph]; LHeC; JET CROSS-SECTIONS; current: high; 7. Clean energy; 13. Climate action